APPROACHES TO MANAGEMENT OF FOREIGN ECONOMIC ACTIVITY OF FIRM IN THE CONDITIONS OF INSTITUTIONAL TRANSFORMATIONS - Oksana Takhumova (Вестник Северо-Кавказского федерального университета, 2022)
The current state of market economy is characterized by strengthening of the international relations which important component is foreign economic activity. Transition to new type of managing demands improvement of the modern mechanism ofmanagement of operations of the enterprises of the external economic complex. In this regard in work classification of the foreign trade transactions, the main components of management, an order offormation of organizational structure offirm is considered. The special attention is paid to structure and the mechanism of effective management offoreign trade activities of economic entities.